Equilibrium trip scheduling in single bottleneck traffic flows considering multi-class travellers and uncertainty – a complementarity formulation - Wang, David Zhiwei (2018)
In this paper, we consider the equilibrium trip scheduling in single bottleneck traffic flows under uncertainty with multi-class travellers. Travel time uncertainty is considered explicitly in the scheduling model, and heterogeneity parameters are assumed to describe the multi-class users. We will present a model applying nonlinear complementarity system approach to formulate and solve the equilibrium trip scheduling problem with multi-class commuters considering travel time uncertainty. The paper presents theoretical proofs for solution existence, and numerical results are conducted to show the model validity.